2010
DOI: 10.5296/npa.v2i2.414
|View full text |Cite
|
Sign up to set email alerts
|

Gradient RSSI Filter and Predictor for Wireless Network Algorithms and Protocols

Abstract: Wireless networks, and in particular Wireless Fidelity (WiFi) networks, present important problems of connectivity among wireless terminals. These problems lead to inefficiencies in the Application level. For localization algorithms in wireless networks, efficient handover protocols and multimedia delivery information, these problems must be solved. A figure used to control the connectivity of terminals to other terminals or to an Access Point (AP) is the well known Received Signal Strength Indicator (RSSI). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Subsequent studies reported that it had a specific effect as an indicator for detecting the decrease in communication link reliability at an early stage, especially when targeting AGVs [17,18]. Furthermore, prediction methods for future RSSI trends have been verified through experiments and simulations [19][20][21][22]. In our proposed method, we also utilize RSSI as an indicator to understand wireless fluctuations.…”
Section: Related Workmentioning
confidence: 89%
“…Subsequent studies reported that it had a specific effect as an indicator for detecting the decrease in communication link reliability at an early stage, especially when targeting AGVs [17,18]. Furthermore, prediction methods for future RSSI trends have been verified through experiments and simulations [19][20][21][22]. In our proposed method, we also utilize RSSI as an indicator to understand wireless fluctuations.…”
Section: Related Workmentioning
confidence: 89%
“…After that, a wireless device that was disconnected from the A j now must be connected to the A i . That process produces a forced handoff (Wang et al 2017) that has been well studied, and efficient traditional solutions exist for it (Suárez et al 2010). For that reason, it is necessary to characterize the trajectory of wireless terminals and efficiently assign the APs of the WiFi network so that the handoff is achieved efficiently.…”
Section: Algorithms For Turning On and Turning Off Aps Of Amentioning
confidence: 99%
“…Received signal strength indicator is one of the most common metrics used in handover decision making [14,[33][34][35]. Through monitoring RSSI via MN, we can analyze the quality and distance for each AP in the range.…”
Section: Tracking Received Signal Strength Indicatormentioning
confidence: 99%